An explorative study of inflammation-related proteins associated with kidney injury in male heat-stressed workers. (February 2023) - Hansson, Erik; Broberg, Karin; Wijkström, Julia; Glaser, Jason; Gonzalez-Quiroz, Marvin; Ekström, Ulf; Abrahamson, Magnus; Jakobsson, Kristina
Abstract: Chronic kidney disease of non-traditional origin (CKDnt) and acute kidney injury (AKI) often affect heat-stressed Mesoamerican manual workers. Inflammation occurs concurrently with AKI in this population, but its role remains unknown. To explore links between inflammation and kidney injury in heat stress, we compared levels of inflammation-related proteins in cutters with and without increasing serum creatinine levels during sugarcane harvest. These sugarcane cutters have previously been identified to be repeatedly exposed to severe heat stress during the five month harvest season. A nested case-control study was conducted among male Nicaraguan sugarcane cutters in a CKDnt hotspot. Cases ( n  = 30) were defined as having an increase in creatinine of ≥0.3 mg/dL across the five-month harvest. Controls ( n  = 57) had stable creatinine levels. Ninety-two inflammation-related proteins in serum were measured before and after harvest using Proximity Extension Assays. Mixed linear regression was used to identify differences in protein concentrations between cases and controls before harvest, differential trends during harvest, and association between protein concentrations and the urine kidney injury markers Kidney Injury Molecule (KIM)-1, Monocyte Chemoattractant Protein (MCP)-1 and albumin. One protein, chemokine (C–C motif) ligand 23 (CCL23), was elevated among cases at pre-harvest. Changes in seven inflammation-related proteins (CCL19, CCL23, colony-stimulating factor 1 [CSF1], hepatocyte and fibroblast growth factors [HGF and FGF23], and tumor necrosis factor beta [TNFB] and TNF-related activation-induced cytokine [TRANCE]) were associated with case status and at least two out of three urine kidney injury markers (KIM-1, MCP-1 and albumin). Several of these have been implicated in myofibroblast activation, which likely is an important step in kidney interstitial fibrotic disease such as CKDnt. This study provides an initial exploration of immune system determinants of, and activation during, kidney injury experienced during prolonged heat stress. Highlights: Inflammation-related protein levels changed with kidney injury during heat strain. CCL23 predicted kidney injury during heat strain, but needs further validation. This explorative study may help identify mechanisms linking heat and kidney injury.